Eye Position Changes during Reading Fixations are Spatially Selective - Inhoff, Albrecht W. (2008)
Intra-fixation location changes were measured when one-line sentences written in lower or aLtErNaTiNg case were read. Intra-fixation location changes were common and their size was normally distributed except for a relatively high proportion of fixations without a discernible location change. Location changes that did occur were systematically biased toward the right when alternating case was read. Irrespective of case type, changes of the right eye were biased toward the right at the onset of sentence reading, and this spatial bias decreased as sentence reading progressed from left to right. The left eye showed a relatively stable right-directed bias. These results show that processing demands can pull the two fixated eyes in the same direction and that the response to this pull can differ for the right and left eye.